Sexual Harassment in Bangladesh: A Note on Legal Perspective - Khan, Md. Mahabub Ul Alam; Halder, Gita Debi (Society & Sustainability, 2022)
This paper offers a description of sexual harassment in Bangladesh. Here the existing laws related to the issue have been analyzed, and a comparative approach to molestation has also been discussed. Different surveys have indicated the increasing rate of sexual harassment in Bangladesh. Countries, such as India, and Pakistan are having specific laws and relevant provisions to mitigate such offenses. Despite having laws regarding such offenses, most countries are unable to fight the social ailment of sexual harassment. The secondary data finds that in 2017, 54.7% of women living in urban areas faced the violence of physical, psychological, financial, and social nature, and received unusual words from the stranger and sometimes also from the known person. Sexual Harassment is taking place in different places including workplaces, educational institutions, and online platforms. The existing legislation regarding such offenses may not be adequate in the current situation as the nature of such offenses has been changed. This paper provides recommendations for amending necessary provisions to mitigate such problems. It highlights different surveys on the issue and elucidates the provisions of sexual harassment. Data have been collected from newspaper articles, journal articles, websites, and case references. The comparative perspective of sexual harassment in different countries has also been discussed in this paper.